Safety experience with continued exposure to ofatumumab in patients with relapsing forms of multiple sclerosis for up to 3.5 years. (September 2022) - Hauser, Stephen L; Cross, Anne H; Winthrop, Kevin; Wiendl, Heinz; Nicholas, Jacqueline; Meuth, Sven G; Giacomini, Paul S; Saccà, Francesco; Mancione, Linda; Zielman, Ronald; Bagger, Morten; Das Gupta, Ayan; et al.
Background: Ofatumumab is approved for the treatment of relapsing multiple sclerosis (RMS). Ongoing safety reporting is crucial to understand its long-term benefit–risk profile. Objective: Report the safety and tolerability of ofatumumab in RMS after extended treatment up to 3.5 years. Methods: Patients completing ASCLEPIOS I/II (phase 3), APLIOS, or APOLITOS (phase 2) trials could enter ALITHIOS, a phase 3b, open-label, long-term safety study. We analyzed cumulative data of continuous ofatumumab treatment and of patients newly switched from teriflunomide. Results: The safety population had 1969 patients: 1292 continuously treated with ofatumumab (median time-at-risk 35.5 months, 3253 patient-years) and 677 newly switched (median time-at-risk 18.3 months, 986 patient-years). A total of 1650 patients (83.8%) had ⩾1 adverse events and 191 (9.7%) had ⩾1 serious adverse events. No opportunistic infections or progressive multifocal leukoencephalopathy events were identified; the risk of malignancies was low. Mean serum immunoglobulin (Ig) G levels remained stable. Mean IgM levels decreased but remained above the lower limit of normal in most. Serious infection incidence was low; decreased Ig levels were not associated with serious infections. Conclusion: In patients with up to 3.5 years' exposure, ofatumumab was well tolerated, with no new safety risks identified. These findings, with its established effectiveness, support a favorable benefit–risk profile of ofatumumab in RMS.